Exploring Sodium Glucose Co-Transporter-2 (SGLT2) Inhibitors for Organ Protection in COVID-19 - Fernandez-Fernandez, Beatriz (J Clin Med, 2020)
Hospital admissions and mortality from the Coronavirus disease 2019 (COVID-19) pandemic are spreading throughout the world, and second and third waves are thought to be likely. Risk factors for severe COVID-19 include diabetes, chronic kidney disease and cardiovascular disease. Currently, there is no vaccine and no approved therapy. Therapeutic approaches are aimed at preventing viral replication and spread, limiting the impact of the inflammatory overdrive (cytokine storm), preventing thromboembolic complications and replacing or supporting organ function. However, despite organ support, mortality is currently 65% for those receiving advanced respiratory support and 78% for those requiring renal replacement therapies. Thus, efforts should be made to provide adjuvant organ protection therapy. This may imply novel therapies in clinical development (e.g., the Fas ligand trap asunercept), but uptake of repurposed drugs already in clinical use may be faster. In this regard, sodium glucose co-transporter-2 (SGLT2) inhibitors were recently shown to protect the heart and kidney both within and outside of a diabetic milieu context. Further, preclinical data support a beneficial effect for the lung. We now discuss the potential benefits and risks of SGLT2 inhibitors in COVID-19 and an ongoing clinical trial testing the impact of dapagliflozin on outcomes in COVID-19 patients with respiratory failure.